Effect of energy level in the diet of indigenous Venda hens on egg production, hatchability and subsequent productivity of the chicks - Maphahla, Vonani Vincent (My University, 2014)
An experiment was conducted to determine the effect of energy level in the diets of indigenous Venda hens on egg production, hatchability and subsequent productivity of the chicks. The first part of the study determined the effect of energy level in the diets of indigenous Venda hens on egg production, hatchability and chick hatch-weight. A total of one hundred hens were randomly assigned to four dietary energy levels, replicated five times with 20 floor pens of 5 birds each. The treatments were CP15 E10 (10 MJ ME/kg DM feed), CP15 E10.5 (10.5 MJ ME/kg DM feed), CP15 E11 (11 MJ ME/kg DM feed) and CP15 E11.5 (11.5 MJ ME/kg DM feed). Energy level in the diets of Venda hens affected (P<0.05) feed intake, egg weight, egg production, egg hatchability and chick hatch-weight. Feed intake and egg weight of Venda hens were optimized at dietary energy levels of 10.70 (r2 = 0.985) and 10.70 (r2 = 0.246) MJ of ME/kg DM, respectively. Strong and positive relationships existed between energy level in the diets of Venda hens’ egg production and egg hatchability. Energy level in the diets of Venda hens affected (P<0.05) egg albumen, yolk and shell weights. Egg albumen, yolk and shell weights were optimized at dietary energy levels of 10.55 (r2 = 0.279), 10.85 (r2 = 0.128) and 10.95 (r2 = 0.863) MJ of ME/kg DM, respectively. Energy level in the diets of Venda hens had no (P>0.05) effect on egg contents. The second part of the study determined the effect of energy levels in the diet of indigenous Venda hens on the performance of progeny chicks aged one to seven weeks. A total of 120 unsexed day-old chicks that hatched from the first part of the study were used according to the treatments and replicates from which they hatched. All the birds were offered the same grower feed and fresh water ad libitum. Energy level in the diet of indigenous Venda hens had no effect on (P>0.05) feed intake, dry matter digestibility, metabolisable energy intake, nitrogen retention and mortality of progenies aged one to seven weeks. However, positive effects (P<0.05) were observed on growth rate, live weight and feed conversion ratio. Live weight, growth rate and feed conversion ratio of Venda chickens were optimized at dietary energy levels of 10.73 (r2 = 0.554), 11.2 (r2 = 0.950) and 11.5 (r2 = 1.000) MJ ME/kg DM, respectively. Male Venda progenies had higher (P<0.05) feed intake, growth rate and live weight, and better (P<0.05) feed conversion ratio than female progenies aged one to seven weeks. The third part of the study determined the effect of energy level in the diets of indigenous Venda hens on the productivity and carcass characteristics of the progeny chickens aged eight to 13 weeks. A 2 (sexes) x 5 (dietary energy levels) factorial arrangement in a completely randomized design was used. Energy level in the diets of Venda hens had no effect (P>0.05) on feed intake, live weight, feed conversion ratio and mortality of their male progenies aged 50 to 91 days. However, male Venda chickens hatched from eggs produced by hens on a diet with 11.5 MJ/kg DM had higher (P<0.05) growth rates than those hatched from eggs produced by hens on a diet with 10.5 MJ/kg DM. Male progenies from hens fed diets having 11.5, 10 or 11 MJ ME/kg DM had the same (P>0.05) growth rates. Similarly, male progenies produced by hens fed diets containing 10, 10.5 or 11 MJ ME/kg had the same (P>0.05) growth rates. Dietary energy levels of the hens had no effect (P>0.05) on feed intake, live weight, feed conversion ratio and growth rate of female Venda chickens aged eight to 13 weeks. Energy level in the diets of Venda hens had no (P>0.05) effect on dry matter digestibility, apparent metabolisable energy and nitrogen retention of their male and female progenies. Venda male progenies were heavier (P<0.05) than female progenies. Male Venda progenies had improved (P<0.05) feed intake, growth rate and feed conversion ratio than female progenies aged eight to thirteen weeks. Energy level in the diets of Venda hens had no effect (P>0.05) on carcass, drumstick, thigh, liver and heart weights of the male progenies aged 91 days. However, energy level in the diets of Venda hens affected (P<0.05) breast, wing, gizzard and fat pad weights of male progenies ages 91 days. Energy level in the diets of Venda hens had no effect (P>0.05) on carcass and carcass weights of female progenies aged 91 days. It is concluded that energy levels of the diets of Venda hens affected egg production, egg weight, egg hatchability and chick hatch-weight. The effects of maternal dietary energy level on intake, live weight and feed conversion ratio of Venda chicken progenies diminished with age.
Thesis (M.A. Agricultural Management ( Animal Production)) -- University of Limpopo, 2014
Keywords: Chicks; Egg production; Indigenous Venda hens; Chicks; Eggs -- Hatchability; Eggs -- Production; Poultry -- Feeding and feeds; Poultry -- Feed utilization efficiency; Poultry -- Hatcheries